2016
DOI: 10.1038/onc.2016.338
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiological implications of the d16HER2 splice variant for stemness and aggressiveness of HER2-positive breast cancer

Abstract: We have previously shown that the d16HER2 splice variant is linked to HER2-positive breast cancer (BC) tumorigenesis, progression and response to Trastuzumab. However, the mechanisms by which d16HER2 contributes to HER2-driven aggressiveness and targeted therapy susceptibility remain uncertain. Here, we report that the d16HER2-positive mammary tumor cell lines MI6 and MI7, derived from spontaneous lesions of d16HER2 transgenic (tg) mice and resembling the aggressive features of primary lesions, are enriched in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 44 publications
3
48
0
Order By: Relevance
“…These genes included epigenetic regulators (for example, JMJD3), genes that control tumor stemness in OC malignancies (for example, HER2), cell proliferation (for example, RB1), apoptosis (for example, BCL-2) and metastasis (for example, MYCN). [12][13][14][15] We found that JMJD3, BCL-2, MYCN, and HER2 levels strongly decreased with Fp-PCN PAC+CAR treatment (Fig. 6C).…”
Section: Jmjd3 As a Novel Target Of Fp-pcn Pac+car In Human Oc Cellsmentioning
confidence: 76%
“…These genes included epigenetic regulators (for example, JMJD3), genes that control tumor stemness in OC malignancies (for example, HER2), cell proliferation (for example, RB1), apoptosis (for example, BCL-2) and metastasis (for example, MYCN). [12][13][14][15] We found that JMJD3, BCL-2, MYCN, and HER2 levels strongly decreased with Fp-PCN PAC+CAR treatment (Fig. 6C).…”
Section: Jmjd3 As a Novel Target Of Fp-pcn Pac+car In Human Oc Cellsmentioning
confidence: 76%
“…A variety of potential molecular mechanisms of resistance to trastuzumab have previously been published, [9][10][11][12] and the vast majority involve the biological functions of breast cancer stem cells (BCSCs). 12,13 Cancer stem cells (CSCs) are a rare fraction of tumour cells that have the abilities of self-renewal, unlimited proliferation and multi-potent differentiation. 14 Like normal tissues, tumour tissues are composed of a variety of heterogeneous tumour cells and originate from corresponding stem cells.…”
mentioning
confidence: 99%
“…90 If patients are first diagnosed with later stages, the 5 year survival rate can be as low as 27%. 95 In fact, it is thought that resistance to monoclonal antibody treatments may be due to inability to bind to this variant form of HER2. For example, the tyrosine kinase receptor HER2 is thought to be overexpressed in up to 30% of patients and is correlated with more aggressive cancer and subsequently increased mortality.…”
Section: Filamentous Phagementioning
confidence: 99%
“…94 Because this variant is found in a majority of patients with HER2-positive breast cancer, it is an attractive target for immunotherapy. 95 In fact, it is thought that resistance to monoclonal antibody treatments may be due to inability to bind to this variant form of HER2. 96 One group created a DNA vaccination that encoded the extracellular and transmembrane domains of Δ16HER2 and demonstrated that following prophylactic immunization, mice were 100% protected from challenge with Δ16HER2-expressing tumor cells for up to 100 days.…”
Section: Filamentous Phagementioning
confidence: 99%